PLANNING AND THE SPATIAL SOLUTION OF FORTIFIED URBAN STRUCTURES IN SECULAR POWER CENTRES BUILT BY THE LIVONIAN BROTHERS OF THE SWORD (1202–1237) - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
On conquered lands inhabited by the Balts, brothers-knights built stone castles with chapels and churches in order to implement Crusaders’ policy. The location of cult buildings adapted to the terrain and traffic roads influenced planning and architectonic space of secular power centres created by the Livonian Brothers of the Sword (Latin: Fratres militiæ Christi Livoniae, German: Schwertbrüderorden; 1202–1237). Research goal: analysis of planning of fortifird urban structures in order to determine the cult buildings’ impact on the layout and the spatial solution of power centres created by the Livonian Brothers of the Sword. Research problem: the influence of cult buildings’ location on construction of power centres designed by the Livonian Brothers of the Sword have not been studied sufficiently. Research novelty: detailed studies of construction of fortified courtyards adapted to the terrain and environment. Research methods: analysis of archive documents, projects and cartographic materials of urban planning, as well as study of published literature and inspection of buildings in nature.